2014
DOI: 10.17219/acem/37239
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Social Support Received by Women in the Perinatal Period

Abstract: Background. Birth of a baby has a big impact on women's lives. The presence and help of loved ones favours wellbeing, health, coping with difficult situations. The aim of this study was to determine whether women's satisfaction with life changes during pregnancy and after delivery, and to identify correlates of life satisfaction. Material and Methods. Life satisfaction was measured using The Satisfaction with Life Scale -SWLS and received social support was assessed using the Berlin Social Support Scales -BSSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 1 publication
2
28
1
6
Order By: Relevance
“…In our study the satisfaction with the life component of wellbeing was reported by some women to be a positive consequence of having a baby, although women were generally not interested in discussing this in detail. Positive perspectives on satisfaction with life are in keeping with other studies on pregnancy and postpartum that suggest that women have a high satisfaction with their life at this time 9,18,19 .…”
Section: Discussionsupporting
confidence: 79%
“…In our study the satisfaction with the life component of wellbeing was reported by some women to be a positive consequence of having a baby, although women were generally not interested in discussing this in detail. Positive perspectives on satisfaction with life are in keeping with other studies on pregnancy and postpartum that suggest that women have a high satisfaction with their life at this time 9,18,19 .…”
Section: Discussionsupporting
confidence: 79%
“…Familial and social support, however, would promote the mother’s well-being and health and strengthen her coping resources [2527]. Adequate support of disabled mothers is therefore an undeniable prerequisite for the establishment of the basic conditions that are critical for children’s positive development, such as bonding, breast-feeding, food preparation and physical care of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Jak wynika z piśmiennictwa satysfakcja z życia kobiet ciężarnych jest zależna od temperamentu, zmiennych emocji, otrzymywanego wsparcia społecznego, stosunków partnerskich czynników socjodemograficznych oraz zmian endokrynologicznych, fizycznych i psychologicznych zachodzące w poszczególnych trymestrach ciąży [4,7,8,9,10].…”
Section: Wprowadzenieunclassified
“…Studies have shown that during pregnancy, women's life satisfaction increases, while in the first years of motherhood, the level of life satisfaction decreases to the level of prior pregnancy [4,5,6]. As it can be seen from the literature, the satisfaction with life of pregnant women is dependent on temperament, variable emotions, received social support, partner, sociodemographic factors and endocrine, physical and psychological changes occurring in individual trimesters of pregnancy [4,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%